Breaking Workplace Silence: How Organizational Communication Reduces The Bystander Effect And Sparks Proactivity: English - Ni Wayan Lasmi; Komang Widhya Sedana Putra P; Wayan Sri Maitri (FAKULTAS DAKWAH UIN SALATIGA, 2025)
In today’s complex and fast-changing work environments, organizations increasingly rely on employees who can take initiative without waiting for instruction. However, this urgency is often undermined by a persistent behavioral pattern: the bystander effect, where individuals hesitate to act due to perceived shared responsibility. While previous research has explored organizational silence and proactivity separately, few studies have examined how internal communication affects proactive behavior through the lens of the bystander effect. This study uses Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data from 200 employees across the public and private sectors in Bali. The results reveal that organizational communication significantly reduces the bystander effect and enhances proactive behavior, both directly and indirectly. The bystander effect is shown to be a meaningful psychological mechanism that mediates these dynamics. Future research should explore how remote work, digital communication, or leadership style influence this relationship over time.